Wittgenstein - Kenny Anthony ("Middlesex, Eng.", 1983)
So much of Wittgenstein's work has now been posthumously published that an overall study is bound to be selective, and so many volumes have been devoted to its elucidation that a new one may well appear superfluous.
Keywords: Wittgenstein Biography